Implementation of Reform Policy: Bureaucracy in Strengthening Resource Shuman Resources in Ternate City - Hendra Karianga; Rasty Amalia; Siti Barora Sinay; M Junaidi (Journal of Law, Politic and Humanities, 2025)
Implementation of Reform Policy: Bureaucracy in Strengthening Resource Shuman Resources in Ternate City. Objective: This study aims to determine the process, identify and analyze aspects that are obstacles in the Implementation of Bureaucratic Reform Policy in Strengthening Human Resources in the Ternate City Inspectorate based on the determining factors for success in the implementation of decentralized policies by G. Shabbir Cheema and Dennis A. Rondinelli. Method: This study was conducted using a qualitative descriptive method to help interpret the phenomena that occur. The theory used is the policy implementation theory according to G. Shabbir Cheema and Dennis A. Rondinelli which consists of environmental conditions, inter-organizational relationships, and characteristics and capabilities of implementing agencies. Results: The results of the study generally indicate that the Implementation of Bureaucratic Reform Policy in Strengthening Human Resources in the Ternate City Inspectorate is running well, but if you look at the impact and performance resulting from bureaucratic reform, it is still slow and not optimal. This is because the overall support for the determining factors for success in policy implementation has not been met, both from environmental conditions, inter-organizational relationships, organizational resources, and characteristics and capabilities of implementing agencies. Conclusion: The suggestion from the research is the need for improvement in work culture commitment, communication, and creating a sense of ongoing involvement, as well as fulfilling the still lacking resources to support effectiveness and smoothness.